Meeting Ethnography Meetings as Key Technologies of Contemporary Governance, Development, and Resistance - Sandler, Jen; Thedvall, Renita (Routledge Research in STEM Education, 2017)
This volume asks and addresses elusive ontological, epistemological, and methodological questions about meetings. What are meetings? What sort of knowledge, identities, and power relationships are produced, performed, communicated, and legitimized through meetings? How do-and how might-ethnographers study meetings as objects, and how might they best conduct research in meetings as particular elements of their field sites? Through contributions from an international group of ethnographers who have conducted "meeting ethnography" in diverse field sites, this volume offers both theoretical insight and methodological guidance into the study of this most ubiquitous ritual.